Evaluasi kebijakan pembangunan puskesmas pembantu di Propinsi Kalimantan Tengah - Kus Winarno; Mubasysyir Hasanbasri; Deni Kurniadi Sunjaya (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: The objective of health development is improving community health status through increasing public access to health services. One of strategy is by supporting facilities forhealth service by developing auxiliary health center for all remote district at Central Kalimantan Province. Central Kalimantan Province with 1,9 million of population, consisted of 14 district, 1348 villages, 805 auxiliary health center. It means that only 59% village have facilities for health service such as auxiliary health center.Objectives: This research aimed to know how formulation process and implementation of policy of developing auxiliary health center by using provincial funds.Method: It was descriptive case study using mainly method qualitative designed by semi structured in-depth interview and document study. Research subject is stakeholder at levelprovince and chosen district. This research executed in Province Public Health Service of Central Kalimantan and one chosen district.Result: Development of secondary health center in Central Kalimantan Province is the realization of Central Kalimantan Province local decree number 12 and 13 year 2005 fulfilmenton RPJPD and RPJMD. Initially, the budgeting concept was planned by Tugas Pembantuan mechanism, but this mechanism was not agreed. This scheme was a top down program fromprovince government. Problems occurred in the implementation are 1). Bad monitoring, 2). Lack of reporting by developer, 3). Remote location of, 4). Varieties in cost of production, 5). Shortage health care workforce, 6). Equipments unmatched the need of health care provider. Evaluation is executed, but only concerning physical progress problem. In the meantime, there was increased allocation of DAK fund in each district.Conclusion: Development of auxiliary health center in Central Kalimantan Province which funded by province fund, is not required by district. There was no agenda surrounding development of auxiliary health center. The role of stakeholder in compilation of agenda setting for this policy was only a normative role.